The Effect of Implemanting E-Filing System, E-Billing System and Understanding of Tax Regulations on Individual Taxpayer Compliance at KPP Pratama Manado - Feibiola Lolombulan; Jessy Warongan; Meily Kalalo (PT FORMOSA CENDEKIA GLOBAL, 2023)
The purpose of this study was to determine the effect of implementing the E-Filing, E-Billing system and understanding of tax regulations on individual taxpayer compliance at KPP Pratama Manado. This type of research is quantitative research by distributing questionnaires. The analytical method used is multiple linear regression analysis with the help of SPPS version 23. The results of this study indicate that the application of the E-Filing system and understanding of tax regulations has a positive effect on individual taxpayer compliance, while the application of the E-Billing system has a negative effect on mandatory compliance. personal tax.